2005
DOI: 10.2486/indhealth.43.320
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral Changes of Shipyard Painters Exposed to Mixed Organic Solvents

Abstract: Abstracts: This study was conducted to evaluate neurobehavioral changes arising from occupational exposure to organic solvents among shipyard painters and to establish whether a dose-effect relation existed where there was any observed impairment of neurobehavioral performance by running the test of Simple Reaction Time (SRT), Symbol Digit Substitution (SD), and Finger Tapping Speed (FT) with a computer-assisted neurobehavioral test battery. The study group consisted of 180 shipyard painters and 60 reference w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
13
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 31 publications
5
13
0
Order By: Relevance
“…This is in concomitant with Crofton et al 1994, who stated that dizziness is an early symptoms due to solvents exposure. Our results are in agreement with Lee et al 2005, who reported that impaired memory, concentration levels and emotional disturbance were the complaints among shipyard painters workers occupationally exposed to toluene.…”
Section: Discussionsupporting
confidence: 93%
“…This is in concomitant with Crofton et al 1994, who stated that dizziness is an early symptoms due to solvents exposure. Our results are in agreement with Lee et al 2005, who reported that impaired memory, concentration levels and emotional disturbance were the complaints among shipyard painters workers occupationally exposed to toluene.…”
Section: Discussionsupporting
confidence: 93%
“…Early studies in Scandinavia suggested that long term, high level, solvent exposure might be associated with a syndrome of personality change, memory impairment, and neurological deficits variously termed chronic toxic encephalopathy (CTE), the psycho-organic syndrome or solvent neurotoxicity [3] The prevalence of individual psychological symptoms were found to be significantly higher among paint manufacturing workers for every question. These results are consistent with the previous studies conducted on spray painters exposed to a mixture of volatile organic solvents and noticed neurobehavioral changes in their neurobehavioral profile [9,10]. From these results, we can conclude that because there are more than nine million workers exposed to solvents in the workplace [11], this population is at risk for a high prevalence of psychiatric problems and the potential for Table 5.…”
Section: Discussionsupporting
confidence: 91%
“…(710,13,15,26,36) Several studies conducted industrial hygiene measurements to be combined with JEMs for deriving a lifetime exposure index. (89,13,36) However, historical trends of solvent air concentration were not considered in those studies. Kishi et al (15) have incorporated the historical changes of solvent air concentrations for estimating solvent exposure indices, but protective equipment use was not considered.…”
Section: Discussionmentioning
confidence: 99%
“…A cumulative lifetime exposure index can be derived by combining chemical measurements and JEMs and has been used in several previous studies of painters and workers at paint manufacturing companies. (79) …”
Section: Introductionmentioning
confidence: 99%